2009
DOI: 10.1097/mpa.0b013e318184d330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicotine and Cigarette Smoke on an Experimental Model of Intraepithelial Lesions and Pancreatic Adenocarcinoma Induced by 7,12-Dimethylbenzanthracene in Mice

Abstract: Nicotine but not cigarette smoke promotes pancreatic DMBA carcinogenesis in mice. Pancreatic adenocarcinomas and PanINs have the same phenotypic appearance as those that occur in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…NIC and other nAChRs agonists in cigarette smoke appear to have an essential role in the pathogenesis of cancer and arteriosclerosis, which were previously believed to be caused primarily by other components of tobacco smoke (i.e. PAHs and nitrosamines) (Bersch et al, 2009;Wong et al, 2007;Egleton et al, 2008;Schuller, 2007Schuller, , 2008Cucina et al, 2008;Lau et al, 2006;Catanzaro et al, 2007;Knaapen et al, 2007;Ramos and Moorthy, 2005;Baird et al, 2005). Furthermore, recent genome-wide association studies have identified single nucleotide polymorphisms (SNP) in 15q24-25 locus (containing the genes for a3, a5 and b4 subunits of nAChRs), which are associated with the risk of lung cancer, arteriosclerosis, and NIC addiction (Thorgeirsson et al, 2008;Amos et al, 2008;Hung et al, 2008;Volkow et al, 2008).…”
Section: Pharmacology and Health Consequences Of Smokingmentioning
confidence: 99%
“…NIC and other nAChRs agonists in cigarette smoke appear to have an essential role in the pathogenesis of cancer and arteriosclerosis, which were previously believed to be caused primarily by other components of tobacco smoke (i.e. PAHs and nitrosamines) (Bersch et al, 2009;Wong et al, 2007;Egleton et al, 2008;Schuller, 2007Schuller, , 2008Cucina et al, 2008;Lau et al, 2006;Catanzaro et al, 2007;Knaapen et al, 2007;Ramos and Moorthy, 2005;Baird et al, 2005). Furthermore, recent genome-wide association studies have identified single nucleotide polymorphisms (SNP) in 15q24-25 locus (containing the genes for a3, a5 and b4 subunits of nAChRs), which are associated with the risk of lung cancer, arteriosclerosis, and NIC addiction (Thorgeirsson et al, 2008;Amos et al, 2008;Hung et al, 2008;Volkow et al, 2008).…”
Section: Pharmacology and Health Consequences Of Smokingmentioning
confidence: 99%
“…But, the model used was relatively consistent with the histopathological features of human PDAC [32], [33]; PanIN grading and the formation of PDAC showed an increasing trend with the extension of DMBA induction time; and CTSE expression level was also gradually increased with the development of lesions. For the transgenic PDAC mouse model, the PDAC and PanINs often show multiple lesions and lack connective tissue hyperplasia; Some genes abnormally expressed in human PDAC are not expressed in the transgenic PDAC mouse model.…”
Section: Discussionmentioning
confidence: 74%
“…Wisniewska et al (13), however, did not differentiate between the different types of pancreatic cells. Cigarette smoke was found not to promote 7,12-dimethylbenzanthracene-induced pancreatic carcinogenesis in mice (14). Cell proliferation was increased in the lung after short-term exposure to cigarette smoke in several studies (7,8,15,16).…”
Section: Discussionmentioning
confidence: 95%